Pandangan Abdullah Saeed Tentang Riba: Teks dan Konteks Ekonomi Islam - Azid, Raka Malik (Al-Muzdahir : Jurnal Ekonomi Syariah, 2024)
The aim of this research is to determine the interpretation of usury using Abdullah Saeed's views. The method used is a qualitative method with a literature review type with data collection techniques using context analysis. The results obtained are that Abdullah Saeed is a Muslim scholar who has the concept of contemporary thought with various brilliant ideas by creating the values ​​of hierarchical principles. Seed has interpreted everything that is still being discussed in circles, one of which is usury. Usury does not necessarily mean that it is haram. According to Saed, there is a need for references from historical narratives to see a problem, such as covering the scope of a law, not necessarily directly legalizing usury law itself. Likewise, humans do not have to always prioritize the `illah aspect (literally in the text of the Qur'an) by ignoring the reasons underlying its interpretation (hikmah). The haram labeling of usury is a view only from the 'god' side, without using wisdom. So, if we look at usury from the perspective of `illat, it is clearly considered haram. However, according to Saeed, the addition of bank interest to debtors is done for a moral aspect. The aspect is mutually beneficial to each other, where the debtor borrows to meet his needs and business, while the institution provides additional fees to the debtor who are due as sanctions and intimation profits to roll back the results of the additional fees